Pengaruh Tingkat Pelanggaran Terhadap Cedera Kepala Pada Kasus Kecelakaan Lalu Lintas Di Kota Denpasar - Prabandari, Gusti Ayu Agung Diah Cahya; Aryani, Putu; Yuliyatni, Putu Cintya Denny; Sucipta Putri, Wayan Citra Wulan (E-Jurnal Medika Udayana, 2023)
Traffic accident is an unexpected event that occurs on the highway usually at a productive age. Traffic accidents occur due to the level of violations committed by the driver. The severity of head injury patients was assessed from the GCS score, namely mild, moderate, and severe head injuries. This study aims to determine the effect of the violations on head injuries in traffic accidents cases in Denpasar City based on age, gender, GCS score, classification of head injuries based on GCS score dan morphology, Mechanism of Injury to assess the level of violations. This research is analytic with cross sectional approach. The data used is secondary data of patients head injuries due to traffic accidents registered in the Medical Records Installation of Sanglah Hospital Denpasar in 2020. The data collection technique by total sampling with the result that 68 data matched inclusion criteria. The results show that most common patient found in the age group 15-24 years(38.2%), male (83.8%), GCS Score 13-15(48.6%), minor violations(33.8%), mild head injury(48.5%) with bleeding morphology(79.4%), and a chi-square test result 0.024 in severe head injuries caused by violation. The conclusion is the most head injury patient due to traffic accidents in Denpasar City are aged 15-24 years, male, GCS score 13-15, commits minor level violations, caused minor head injury with bleeding morphology, and result of chi-square test show that level of violation affect head injury. The result of this study can be developed and become the basis for the other research with more varied variables. Keywords : Traffic Accident, Violation Rate, Head Injury